Analisis Literatur Tentang Strategi Pemasaran Mixue Dan Hubungannya Dengan Minat Beli Ulang Konsumen - Nuviah Herawati; Arief Dermawan; Agung Hartadi (STIE Pariwisata API Yogyakarta, 2024)
Repurchase interest is very important for food and beverage producers, one of which is Mixue products, so that they can survive and grow. To grow consumer repurchase interest, a marketing mix strategy is used using 4 concepts, namely product, price, place and promotion. This study aims to determine the effect of product, price, place and promotion on repurchase interest. This study uses article reviews as its data source, by collecting, selecting and then analyzing articles that have topics relevant to the problems studied and conclusions are obtained from the analysis. Using 10 articles that conducted research at Mixue outlets in 10 different regions in Indonesia. From the review of these articles, the results showed that product, place and promotion had a significant effect on repurchase interest in Mixue products, but for price, some concluded that this variable had no significant effect on repurchase, as well as place when given lifestyle moderation, it had no effect on repurchase interest. Future research on price variables can be further studied because there are differences in findings in certain areas, and further researchers can add other variables that can affect repurchase interest in Mixue products and in using marketing strategies, the 7p concept can be used to increase solutions to overcome this problem.